The severity of coronary artery disease was not associated with non-alcoholic fatty liver disease in a series of 264 non-diabetic patients who underwent coronary angiography - Langroudi Taraneh Faghihi; Haybar Habib; Parsa Saeed Alipour; Mahjoorian Mohamad; Khaheshi Isa; Naderian Mohammadreza (Sciendo, 2018)
Background. It is now suggested an association between non-alcoholic fatty liver disease (NAFLD) and the occurrence of coronary artery disease even in non-diabetic patients. We will determine the rate of NAFLD and its main determinants in non-diabetic patients undergoing coronary angiography.